Compliance checking of software processes: A systematic literature review. Issue 5 (14th March 2022) - Castellanos Ardila, Julieth Patricia; Gallina, Barbara; Ul Muram, Faiz
Abstract: The processes used to develop software need to comply with normative requirements (e.g., standards and regulations) to align with the market and the law. Manual compliance checking is challenging because there are numerous requirements with changing nature and different purposes. Despite the importance of automated techniques, there is not any systematic study in this field. This lack may hinder organizations from moving toward automated compliance checking practices. In this paper, we characterize the methods for automatic compliance checking of software processes, including used techniques, potential impacts, and challenges. For this, we undertake a systematic literature review (SLR) of studies reporting methods in this field. As a result, we identify solutions that use different techniques (e.g., anthologies and metamodels) to represent processes and their artifacts (e.g., tasks and roles). Various languages, which have diverse capabilities for managing competing and changing norms, and agile strategies, are also used to represent normative requirements. Most solutions require tool‐support concretization and enhanced capabilities to handle processes and normative diversity. Our findings outline compelling areas for future research. In particular, there is a need to select suitable languages for consolidating a generic and normative‐agnostic solution, increase automation levels, tool support, and boost the application in practice by improving usability aspects. Abstract : This paper presents a systematic literature review where we identified a diversity of solutions for automated compliance checking. Most solutions require tool‐support concretization and enhanced capabilities to handle processes and normative diversity. Our findings outline compelling areas for future research. In particular, there is a need to select suitable languages for consolidating a generic and normative‐agnostic solution, increase automation levels, tool support, and boost the application in practice.